Advance in research on the influence of mind-body exercise on anxiety symptoms in patients with Parkinson's disease (身心运动对帕金森病患者焦虑症状影响的研究进展) - XU Xingyi (徐星怡); SHEN Xuhui (沈旭慧); CHEN Haiqin (陈海勤); XU Jiali (徐嘉莉); QIAN Xia (钱霞) (中西医结合护理)
Neuropsychiatric symptoms occur in the majority of patients with Parkinson's disease (PD). It is one of the most common causes of disability. This paper reviews the mind-body exercise methods affecting anxiety symptoms in PD patients at home and abroad, including Tai Chi, Baduanjin, Wuqinxi, and mindfulness yoga, in order to provide inspiration for constructing the intervention program for non-exercise symptoms in PD patients, reduce disability rate and improve quality of life. (神经精神症状(NPS)在帕金森病(PD)患者的病程中常见, 是导致患者残疾的原因之一。本研究就国内外影响PD患者焦虑症状的身心运动方法进行综述, 包括太极拳、八段锦、五禽戏、正念瑜伽, 以期为构建PD患者非运动症状干预方案提供启发, 降低致残率, 提高生存质量。)